'The Man Will Shame Me': Women, Sex and Kirk Discipline during the Cromwellian Occupation. Issue 2 (September 2022) - Brock, Michelle D.
Abstract : This article explores the experiences of Scottish women and their interactions with the Kirk during the Cromwellian occupation. Drawing on kirk session records, it demonstrates that amid the heightened anxieties of the 1650s, parish kirks viewed and treated female bodies as potential sources of social and religious disorder. This analysis reveals the strength of the Kirk's regulatory toolkit in times of crisis as well as the continuity of gendered experiences of discipline. It also offers new insights into civilian experiences of the Cromwellian invasion.